2016
DOI: 10.1200/jco.2016.66.9010
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Irinotecan Plus Cisplatin Compared With Paclitaxel Plus Carboplatin As First-Line Chemotherapy for Ovarian Clear Cell Carcinoma: JGOG3017/GCIG Trial

Abstract: No significant survival benefit was found for CPT-P. Both regimens were well tolerated, but the toxicity profiles differed significantly. Treatment with existing anticancer agents has limitations to improving the prognosis of CCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 29 publications
4
88
0
Order By: Relevance
“…Lastly, contrary to the expectations from the promising results of the previous randomized phase II study (JGOG3014) [34], which showed a tendency of PFS superiority of the irinotecan plus cisplatin group compared with paclitaxel plus carboplatin group in a subset analysis of ovarian clear cell carcinoma (CCC) patients without residual disease or with residual disease <2 cm, a randomized phase III trial of irinotecan plus cisplatin compared with paclitaxel plus carboplatin as first-line chemotherapy for CCC (JGOG3017) failed to show significant survival benefit between the groups [35]. In this study, a total of 667 ovarian CCC patients were randomized to receive irinotecan 60 mg/m 2 (day 1, 8, and 15) plus cisplatin 60 mg/m 2 (day 1) every 4 weeks or paclitaxel 175 mg/m 2 plus carboplatin AUC 6 every 3 weeks.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Lastly, contrary to the expectations from the promising results of the previous randomized phase II study (JGOG3014) [34], which showed a tendency of PFS superiority of the irinotecan plus cisplatin group compared with paclitaxel plus carboplatin group in a subset analysis of ovarian clear cell carcinoma (CCC) patients without residual disease or with residual disease <2 cm, a randomized phase III trial of irinotecan plus cisplatin compared with paclitaxel plus carboplatin as first-line chemotherapy for CCC (JGOG3017) failed to show significant survival benefit between the groups [35]. In this study, a total of 667 ovarian CCC patients were randomized to receive irinotecan 60 mg/m 2 (day 1, 8, and 15) plus cisplatin 60 mg/m 2 (day 1) every 4 weeks or paclitaxel 175 mg/m 2 plus carboplatin AUC 6 every 3 weeks.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Irinotecan hydrochloride, inhibiting topoisomerase I, is one of the key anticancer drugs in chemotherapy for several cancers such as colorectal cancer, lung cancer, gastric cancer, and gynecologic cancers 14. The patients treated with irinotecan occasionally experience severe neutropenia and delayed diarrhea; however, the occurrence of these adverse reactions has been unpredictable and largely unexplained 5.…”
Section: Introductionmentioning
confidence: 99%
“…3Y5 A recent randomized phase III clinical trial comparing the efficacy of irinotecan plus cisplatin to that of paclitaxel plus carboplatin in patients with OCCC [Japanese Gynecologic Oncology Group (JGOG) 3017/ Gynecologic Cancer Intergroup (GCIG) Trial] failed to observe a significant survival benefit with irinotecan plus cisplatin. 6 Therefore, effective and novel treatment strategies, such as incorporation of molecular-targeted agents to current protocols, are urgently needed to improve outcomes for patients with advanced OCCC.…”
mentioning
confidence: 99%